Resveratrol drives ferroptosis of acute myeloid leukemia cells through Hsa-miR-335-5p/NFS1/ GPX4 pathway in a ROS-dependent manner: Resveratrol drives ferroptosis of acute myeloid leukemia cells - Liu, Jia; Gao, Wei; Sheng, Yong; Sun, Jiafeng; Wen, Donghu (Cellular and Molecular Biology, 2023)
To explore the potential target to induce ferroptosis for treating acute myeloid leukemia (AML) as well as its mechanism and latent drugs. Using the keyword “acute myelogenous leukemia”, the related dataset in TCGA and GEO were used for searching differentially expressed genes. After the filtrate by ROC curve, AUC values, and survival analysis, RT-qPCR as well as Western-blot analysis were performed to verify the high expression level of NFS1 in AML-193 and OCI-AML-3 cells. After CCK-8 detection with and without various cell death inhibitors, ferroptosis were further detected by the expression level of GPX4. After taking the intersection in Starbase and TargetScan, the upstream regulatory miRNA of NFS1 was found. Then the relation of hsa-miR-335-5p, NFS1, as well as GPX4, was ascertained by knockdown and overexpression study in AML-193 and OCI-AML-3 cells. In addition, cellular ROS was detected by DCFH-DA. Finally, resveratrol was used to intensify ferroptosis of AML-193 and OCI-AML-3 cells. NFS1 was highly expressed in AML cells, positively associated with AML-related mortality, and can be used to diagnose AML. Knockout of NFS1 facilitated ROS accumulation and ferroptosis-associated labile iron pool increase. si-NFS1 can inhibit the expression level of GPX4, facilitate ROS accumulation and induce ferroptosis-associated labile iron pool increase. Besides, overexpressed GPX4 can lead to down-regulated cell death after si-NFS1 treatment. Hsa-miR-335-5p was found as the upstream regulator of NFS1. The expression of NFS1 can be up-regulated by sh-hsa-miR-335-5p transfection and can be inhibited by hsa-miR-335-5p transfection. Resveratrol was found can increase the expression level of hsa-miR-335-5p and decrease the expression of NFS1 and GPX4. Resveratrol can intensify ferroptosis of AML cells via Hsa-miR-335-5p/NFS1/ GPX4 pathway through a ROS-dependent manner.